New malic acid producer strains of Saccharomyces cerevisiae for preserving wine acidity during alcoholic fermentation. (June 2023) - Vion, Charlotte; Muro, Maitena; Bernard, Margaux; Richard, Bruce; Valentine, Fautre; Yeramian, Nadine; Masneuf-Pomarède, Isabelle; Tempère, Sophie; Marullo, Philippe
Abstract: In the context of climate change, the chemical composition of wines is characterized by a massive drop of malic acid concentration in grape berries. Then wine professionals have to find out physical and/or microbiological solutions to manage wine acidity. The aim of this study is to develop wine Saccharomyces cerevisiae strains able to produce significant amount of malic acid during the alcoholic fermentation. By applying a large phenotypic survey in small scale fermentations, the production level of malic acid in seven grape juices confirmed the importance of the grape juice in the production of malic acid during the alcoholic fermentation. Beside the grape juice effect, our results demonstrated that extreme individuals able to produce up to 3 g/L of malic acid can be selected by crossing together appropriate parental strains. A multivariate analysis of the dataset generated illustrate that the initial the amount of malic acid produced by yeast is a determining exogenous factor for controlling the final pH of wine. Interestingly most of the acidifying strains selected are particularly enriched in alleles that have been previously reported for increasing the level of malic acid at the end of the alcoholic fermentation. A small set of acidifying strains were compared with strains able to consume a large amount of malic acid previously selected. The total acidity of resulting wines was statistically different and a panelist of 28 judges was able to discriminate the two groups of strains during a free sorting task analysis. Highlights: The initial amount of malic acid of grape juices is a major factor affecting the metabolism of malic acid by Saccharomyces cerevisiae strains. By implementing a breeding program several strains producing more than 3 g/L of malic acid have been selected paving a new avenue for managing wine acidity during the alcoholic fermentation. The impact of some QTLs linked to malic acid has been validated in high producer strains. Strains with different malic acid metabolism impact the acidity perception of the resulting wines.